Analysis of Bicarbonate-Based Purge Solution in Patients With Cardiogenic Shock Supported Via Impella Ventricular Assist Device. Issue 6 (June 2023) - Bergen, Kyle; Sridhara, Shashank; Cavarocchi, Nicholas; Silvestry, Scott; Ventura, Davide
Background: The Impella device is a continuous axial flow pump which provides hemodynamic support by expelling blood into the aorta. The manufacturer recommends using dextrose-based heparin containing solutions as the default purge. As an alternative to anticoagulant solutions, a bicarbonate-based purge solution has been proposed with limited data substantiating adequate protection and durability. Objective: To assess the impact of a bicarbonate-based purge solution on Impella pump thrombosis and bleeding outcomes. Methods: Single-center, retrospective study of cardiogenic shock patients who received an Impella between December 2020 through September 2021. Patients were evaluated based on whether they received bicarbonate-based purge solutions or remained on heparin-based purge solutions. The primary outcome was the rate of Impella pump thrombosis, defined as multiple purge pressures greater than 800 mm Hg. Secondary outcomes included incidence of bleeding defined as a drop in Hgb of at least 2 g/dL along with use of blood products and supratherapeutic anticoagulation defined as an aPTT of greater than 70 seconds. Results: Forty-three patients received bicarbonate-based purge solutions and 49 controls received heparin. The incidence of purge thrombosis by purge pressure threshold was similar between the two groups (16.3% vs 12.2%, P = 0.58). The rate of bleeding was lower with bicarbonate-based purge (27.9% vs 65.3%, P < 0.05) driven by a drop in Hgb of more than 2 g/dL. The rate of supratherapeutic anticoagulation was higher in the heparin arm (65.3% vs 27.9%, P < 0.05) Conclusion and Relevance: Nonanticoagulant purge alternatives offer the potential to reduce bleeding complications and laboratory monitoring burden while maintaining durability.